Evaluation of Ultrasound-Guided Versus Landmark based peripheral nerve blocks in upper limb Surgeries - Iram Shahzadi, Yasmeen Afridi, Khurram Liaqat, Sayed Makarrom Bukhari, Abdul Basit Gillani, Asad Ahmed Sheikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Peripheral nerve blocks are widely used for upper limb surgeries, yet the effectiveness of traditional landmark-based techniques remains limited by anatomical variability and lack of visualization. Objective: This study compared the clinical performance and postoperative outcomes of ultrasound-guided versus landmark-based peripheral nerve blocks. Methods: A comparative study was conducted at CMH, Muzaffarabad (AJK) from January 2023 to June 2023 among 220 patients undergoing upper limb surgeries, with 110 receiving ultrasound-guided blocks and 110 receiving landmark-based blocks. Data included demographic variables, block performance characteristics, postoperative analgesia, patient satisfaction, and procedural complications. Results: Ultrasound-guided blocks showed significantly higher success rates (93.6% vs. 77.3%; p < 0.001), shorter block performance time (6.8 ± 2.1 min vs. 9.4 ± 2.7 min; p < 0.001), and faster sensory and motor onset. The duration of postoperative analgesia was markedly longer in the ultrasound group (11.4 ± 3.2 hours vs. 8.1 ± 2.9 hours; p < 0.001). Complications such as vascular puncture (3.6% vs. 13.6%) and hematoma (1.8% vs. 7.3%) were significantly lower in the ultrasound-guided group. Patient satisfaction scores were notably higher with ultrasound guidance (9.1 ± 1.0 vs. 7.6 ± 1.4; p < 0.001). Conclusion: It is concluded that ultrasound-guided peripheral nerve blocks provide superior accuracy, safety, analgesic duration, and patient satisfaction compared with landmark-based techniques. Keywords: Nerve block, limb, Surgery, patients, Visualization, Anatomical, Peripheral